التعبيرات اللغوية المستخدمة في المواقف الإجتماعية : دراسة تحليلية تعليمية - معلم، أحمد محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
This study collects different linguistic expressions used in social situations in some Arab countries like Egypt, Iraq, Algeria, Saudi Arabia, and Lebanon. It analyzes the social and cultural characteristics of these expressions and the different dialectical changes resulting from varying usage of these expressions in different countries. It compares these expressions with the standard Literary Arabic expressions and identifies the pitfalls in these linguistic expressions. Finally, it discusses the methodology of how to better teach these standard expressions to non- Arabic speakers. The study applied the descriptive and analytical methodology. The data were collected from the Arab native speakers from the above mentioned countries through a questionnaire and interviews, which were self administrated. In addition, the study benefited from books and periodicals. The study found as follows: One, the socio- linguistic expressions constitute a part of the people's life, and their culture. Two, the socio-linguistic expressions are a result of language development and movement towards its simplification and usage. Three, and correct usage of these expressions by non-native Arabic speakers well enhance social and psychological understanding and promote better rapport between the native and non native speakers of the Arabic language.